2012
DOI: 10.5005/jp-journals-10024-1222
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Activity of the Three Commercially Available Intense Sweeteners against Common Periodontal Pathogens: An in vitro Study

Abstract: Aim To evaluate the in vitro antimicrobial activity of three commercially available intense sweeteners against two common periodontal pathogens Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans. Materials and methods Three commercially available intense sweeteners namely saccharin, aspartame and sucralose were obtained and powdered. Necessary concentrations of the sweeteners were prepared by mixing them with an inert solvent. The antimicrobial efficacy was assessed using agar well diffusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 9 publications
0
10
0
4
Order By: Relevance
“…Saccharin, Aspartame, and Sucralose have bacteriostatic impact on oral microorganisms. 21 Saccharin and Acesulfame-K invigorate adipogenesis through AKT (protein kinase B) flagging. 19 In human investigations, NNS has appeared to bring down BMI in overweight kids and incomprehensibly expands BMI in normal weight kids and builds the danger of metabolic disorder in grown-ups.…”
Section: Consequences O F Nonnutritive Sugars Consumption I N Animalsmentioning
confidence: 99%
“…Saccharin, Aspartame, and Sucralose have bacteriostatic impact on oral microorganisms. 21 Saccharin and Acesulfame-K invigorate adipogenesis through AKT (protein kinase B) flagging. 19 In human investigations, NNS has appeared to bring down BMI in overweight kids and incomprehensibly expands BMI in normal weight kids and builds the danger of metabolic disorder in grown-ups.…”
Section: Consequences O F Nonnutritive Sugars Consumption I N Animalsmentioning
confidence: 99%
“…These have looked at their effects on secretion, absorption, gut motility, the microbiome and gastrointestinal symptoms [156,157,158,159,160]. Some studies imply that ASs have measurable effects on the oral/gut microbiota [155,161,162]. In one example, male rats were randomised into control and AS groups and were exposed to doses ranging from 1.1 to 11 mg/kg/day for 12 weeks (the USA Federal Drug Administration (FDA) acceptable daily intake for humans is 5 mg/kg/day).…”
Section: The Western Dietmentioning
confidence: 99%
“…However, further research in healthy human subjects continues to suggest that microbiota are adversely affected by ASs. Suez and colleagues showed that with 11 weeks of exposure to three common ASs, saccharin altered gut microbiota and induced glucose intolerance [161]. This indicates the need for more studies—particularly in humans—to elucidate the effects of ASs on microbiota [164,165,166].…”
Section: The Western Dietmentioning
confidence: 99%
“…After subsequent studies failed to confirm a link between o-benzoic sulfimide and bladder cancer in humans, saccharin was removed from the list of potential carcinogens in the year 2000 [17]. The current United States Food and Drug Administration (FDA) confirms the acceptable daily intake (ADI) of 15 milligrams per kilogram body weight per day (mg/kg bw/d) as safe in humans [18][19][20][21][22][23][24][25][26][27][28]. During the same period, studies revealed a relationship between gut microbiome perturbed by saccharin and the expression of pro-inflammatory cytokine-inducible nitric oxide synthase (iNOS) and tumor necrosis factor (TNF-α) in the liver [19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The current United States Food and Drug Administration (FDA) confirms the acceptable daily intake (ADI) of 15 milligrams per kilogram body weight per day (mg/kg bw/d) as safe in humans [18][19][20][21][22][23][24][25][26][27][28]. During the same period, studies revealed a relationship between gut microbiome perturbed by saccharin and the expression of pro-inflammatory cytokine-inducible nitric oxide synthase (iNOS) and tumor necrosis factor (TNF-α) in the liver [19][20][21][22][23][24][25][26][27][28]. Subsequent studies have shown that o-benzoic sulfimide and its derivatives in concentrations from 1 to 320 mg/mL may have different inhibitory efficiencies on different bacterial species in vitro and in vivo [20][21][22][23][24]28,29].…”
Section: Introductionmentioning
confidence: 99%